Changes in peripheral innervation and nociception in reticular type and erosive type of oral lichen planus - Siriporn Chattipakorn; Jitjiroj Ittichaicharoen; Samreung Rangdaeng; Nipon Chattipakorn (Wolters Kluwer Medknow Publications, 2011)
Background: Oral lichen planus (OLP) is a chronic inflammatory lesion in oral mucosa. Reticular (OLP-R) and erosive (OLP-E) types of OLP are the common forms that have been found in dental clinics. The aim of this investigation is to determine the correlation between neurogenic inflammation and nociception associated with OLP-R and OLP-E. Materials and Methods: The oral mucosal lesions from six patients with OLP-E, four with OLP-R and three with noninflamed oral mucosa, which represent normal mucosa, were identified by morphometric analysis of nerve fibers containing immunoreactive protein gene product (PGP) 9.5. The level of inflammation was measured with hematoxylin and eosin staining and the level of nociception was analyzed with visual analog scale measurement. Results: We found that 1) an increase in peripheral innervation was related to the size of the area of inflammatory cell infiltration from both OLP-R and OLP-E; 2) the pattern of PGP 9.5-immunoreactivity among OLP-R and OLP-E was not significantly different (P=0.23); and 3) the correlation between nociception and an increase in PGP 9.5-immunoreactivity was not found in OLP-E and in OLP-R. Conclusions: Our findings suggest that an increase in peripheral innervation may lead to increased inflammation, which is part of the immunopathogenesis of OLP. Differences in nociception between OLP-R and OLP-E arise from the pathogenesis of each lesion, not from the differences in peripheral innervation.